Taxonomy of mycelial actinobacteria isolated from Saharan soils and their efficiency to reduce aflatoxin B1 content in a solid-based medium - Lahoum, Abdelhadi; Verheecke-Vaessen, Carol; Bouras, Noureddine; Sabaou, Nasserdine; Mathieu, Florence (Elsevier, 2017)
Aflatoxin B1 (AFB1) is a carcinogenic compound produced by filamentous fungi. In order to reduce AFB1 occurrence in foodstuffs, 13 strains of mycelial actinobacteria were tested in vitro for the efficacy to reduce AFB1 content; all were isolated from the Saharan soils of Algeria. Firstly, morphological study and molecular analysis, based on the 16S rRNA gene, indicated that these strains belong to Actinomadura, Nocardiopsis, Nonomuraea, Saccharothrix and Streptomyces genera. Secondly, each strain’s efficacy to reduce pure AFB1 content was studied in ISP2-medium. After a 4-day incubation at 30°C on AFB1-supplemented medium (5 ppm of AFB1), AFB1 was extracted and quantified. AFB1 content was reduced by all strains (42.9–97.6%). The three most efficient reducers (94.9–97.6%) were two strains belonging to the genus Streptomyces and one to the genus Saccharothrix. Among the latter, strains ACD6 and ABH19 showed no adsorption mechanism involved, suggesting a potential degradation mechanism. These findings led us to suggest that these actinobacterial strains could be used as decontamination treatments for the reduction of AFB1 content.
Keywords: Mycelial actinobacteria; Taxonomy; Molecular identification; Aflatoxin B1 decontamination